3D Modelling and Visualization in Field Archaeology. From Survey To Interpretation Of The Past Using Digital Technologies - Daniele Ferdani; Emanuel Demetrescu; Marco Cavalieri; Gloriana Pace; Sara Lenzi (Groma, 2020)
Over the last few decades, there has been a growing interest in the fusion of the humanities and the hard sciences. The continuous experimentation and contamination between these two disciplines has led to the emergence of new horizons of research and open to perspectives and issues previously unthinkable. Finally, it has started the development of specific technologies for the cultural domain. Among these technologies, virtual archaeology, which we could define as the set of processes of acquisition, analysis and interpretation aimed at visualizing and simulating the past using 3D digital technologies and a theoretical and multidisciplinary scientific approach, has now reached its maturity. In this contribution the potentials in using 3D modelling as a tool of investigation and visualization for a deeper understanding of archaeological sites is presented. The discussion is supported by the case study of the roman villa of Aiano, built at the beginning of the 4th century A.D. and characterized by monumental architecture and decorations.